In Search of Fiscal Space in Africa: The Role of the Quality of Government Spending - (:unkn) unknown (My University, 2015)
Taking advantage of African experience, this paper proposes to enrich empirically the issue of fiscal space. Africa has markedly achieved significant economic progress since the 80's decade crisis. However, this progress has been proven insufficient to curb dramatically the infrastructures gap and poverty because of the shortage of funding. While several ways are being looked for creating a sustained fiscal space, this paper argues that improving the quality of public spending remains the key avenue. It then derives fiscal space by computing Data Envelopment Analysis (DEA) efficiency scores of public spending using a group of 62 African and non-African countries over the period 1980-2013. The results indicate that on average African countries are less efficient than their peers. The average efficiency score of public spending for African countries relatively to their peers is 0.585 suggesting that they could reduce their spending by 41.5% to achieve the same results. This results in a lost fiscal space of about 11.5% of GDP equivalent to 43.8% of the outlay used and 3/4 of the current level of tax revenues. However, they have achieved a substantial improvement in efficiency change over time. Moreover, the results evidence that this estimated lost fiscal space is tied to the other indicators of fiscal space. In particular, larger lost fiscal space is positively correlated with foreign aid and external debt inflows but negatively with tax capacity.
Keywords: African Research